An overview on monkeypox virus: Pathogenesis, transmission, host interaction and therapeutics - Rampogu, Shailima; Kim, Yongseong; Kim, Seon-Won; Lee, Keun Woo (Frontiers in Cellular and Infection Microbiology, 2023)
In the recent times Monkeypox (MP) is a zoonotic disease that has been spreading outside Africa. The spread is global and the reports of infections are increasing every day. While the medication to this is limited, it is essential to know the modes of transmission and symptoms in order to halt the spread of the disease. In the current review, we have highlighted the MPV structure, its transmission modes and available therapeutic options. We have also highlighted the host-virus interaction. Furthermore, this review provides an insight for the scientific community for extending their research work in this field.